The role of sleep disorders and depression in predicting suicidal ideation inpatients with multiple sclerosis - ZakibakhshMohammadi, Nasim; Mikaeili, Niloofar; Kianimoghadam, Amir Sam; Hazrati, Sajad (Researcher Bulletin of Medical Sciences, 2024)
Background: Due to the higher prevalence of suicidal ideation in patients with multiple sclerosis compared to the general population and the prevalence of sleep disorders and depression in these patients and the role of sleep disorders and depression in the incidence of suicidal ideation this study aimed to investigate the role of sleep disorders and depression in multiple sclerosis. Materials and Methods: The method of the present study was a cross-sectional descriptive correlational study. The population of the present study consisted of patients with multiple sclerosis who were selected by using the inclusion criteria in the winter of 1400 and 252 people filled the Suicide Behaviors Questionnaire-Revised (SBQ R), the Mini sleep Questionnaire (MSQ), and the Patient Health Questionnaire-9 (PHQ-9) by online available methods. Results: The findings show the sleep disorder variable was able to explain 0.037% of the variance of suicidal ideation (R2 = 0.037) and depression was able to predict 0.070% of the variable of suicidal ideation. Conclusion: According to the research findings it may be effective to consider treatments for sleep disorders and depression in patients with MS, especially in the first few years of receiving the diagnosis to prevent suicidal ideation.